Perception of the quality of life of caregivers of octogenarians - Camila Alves Nogueira; Fabiana Paulino Alves; Alexsandro Silva Coura; Caroline Evelin Nascimento Kluczynik Vieira; Bertha Cruz Enders; Inacia Sátiro Xavier de França (Rev Rene)
The objective of the study was to investigate the perception that caregivers of octogenarians have regarding the quality of life and aspects of life that are more harmful to this quality. A cross-sectional, descriptive and quantitative study conducted in 2010 with 52 subjects of the Family Health Units in Campina Grande-PB, Brazil that responded a socio-demographic questionnaire and the WHOQOL-Bref. Data were analyzed with the SPSS. The total WHOQOL-bref score was 52.26 points. The aspects that were more jeopardized were: sex life (94.3%), feelings (67.4%), pain (65.5%) and leisure (53.8%); the least affected were: living quarters (82.8%), energy (78.9%), physical appearance (78.9%) and personal relationships (76.9%). The caregivers’ perceptions regarding the quality of life are marked by dissatisfaction, thereby leading to the belief that the care activities can have a negative effect on their lives.